Politeness in Digital Conversations: A Linguistic Analysis of Prilly Latuconsina’s Utterances in a TikTok Podcast and Their Relevance to Language Education - Sari, Lusi Komala; Sifa, Nazwa Ainis; Onwuagboke, Bede Blaise Chukwunyere (Actual Insight, 2025)
In the era of digital communication, language use in public discourse has shifted significantly, especially through platforms such as podcasts that promote informal yet influential conversations. This study aims to identify and analyze the politeness strategies employed by Prilly Latuconsina, a public figure, in a podcast hosted by Dedy Corbuzier and Vidi Aldiano. Using a pragmatic approach grounded in Geoffrey Leech’s (1983) politeness maxims, this qualitative study examines 150 utterances from the podcast transcript to determine the forms and frequency of politeness strategies in Prilly’s speech. The results show that she consistently applies the maxims of tact, approbation, modesty, sympathy, and agreement, predominantly using tact and approbation to construct a positive public image and maintain harmonious interactions. These findings suggest that public figures can serve as effective pragmatic models for formal education, particularly in teaching politeness strategies within Bahasa Indonesia language classes and university-level pragmatics and rhetoric courses. By integrating authentic digital discourse into language instruction, this research supports the development of students’ communicative competence in meaningful and context-rich ways, highlighting the pedagogical potential of podcast-based materials.